Identification of two chickpea multidrug and toxic compound extrusion transporter genes transcriptionally upregulated upon aluminum treatment in root tips - Jia, Yong; Pradeep, Karthika; Vance, Wendy H.; Zhang, Xia; Weir, Brayden; Wei, Hongru; Deng, Zhiwei; Zhang, Yujuan; Xu, Xuexin; Zhao, Changxing; Berger, Jens D.; Bell, Richard William; et al. (Frontiers in Plant Science, 2022)
Aluminium (Al) toxicity poses a significant challenge for the yield improvement of chickpea, which is an economically important legume crop with high nutritional value in human diets. The genetic basis of Al-tolerance in chickpea remains unclear. Here, we assessed the Al-tolerance of eight wild Cicer and one cultivated chickpea (PBA Pistol) accessions by measuring the root elongation in solution culture under control (0 µM Al3+) and Al treatments (15, 30 µM Al3+). Compared to PBA Pistol, the wild Cicer accessions displayed both tolerant and sensitive phenotypes, supporting wild Cicer as a potential genetic pool for Al-tolerance improvement. To identify potential genes related to Al-tolerance in chickpea, genome-wide screening of multidrug and toxic compound extrusion (MATE) encoding genes was performed. Fifty-six MATE genes were identified in total, which can be divided into 4 major phylogenetic groups. Four chickpea MATE genes (CaMATE1-4) were clustered with the previously-characterized citrate transporters MtMATE66 and MtMATE69 in Medicago truncatula. Transcriptome data showed that CaMATE1-4 have diverse expression profiles, with CaMATE2 being root-specific. qRT-PCR analyses confirmed that CaMATE2 and CaMATE4 were highly expressed in root tips and were up-regulated upon Al treatment in all nine chickpea lines. Further measurement of carboxylic acids showed that malonic acid, instead of malate or citrate, is the major extruded acid by Cicer spp. root. Protein structural modelling analyses revealed that CaMATE2 has a divergent substrate-binding cavity from Arabidopsis AtFRD3, which may explain the different acid-secretion profile for chickpea. Pangenome survey showed that CaMATE1-2 have much higher genetic diversity in wild Cicer than that in cultivated chickpea. This first identification of CaMATE2 and CaMATE4 responsive to Al3+ treatment in Cicer paves the way for future functional characterization of MATE genes in Cicer spp., and to facilitate future design of gene-specific markers for Al-tolerant line selection in chickpea breeding programs.